Pembunuhan Tidak Disengaja Ditinjau Dari Hukum Pidana Menurut Pasal 351 KUHP (Studi Kasus: Putusan No 1/Pid.B/2022/Pn Amb) - Juniati Laora Garoma; Julianus Edwin Latupeirissa; Iqbal Taufik (Faculty of Law Universitas Pattimura, 2023)
ABSTRACT: This research discusses the cases contained in the court decision No 1/Pid.B/2022/Pn Amb. Where Schwarcof Etus Kainama died with the perpetrator being Heron Doweeks Pattiwael who was sentenced to 4 (four) years in prison by the Ambon District Court Judge for being proven guilty of violating article 351 concerning severe maltreatment resulting in death. In this case, there was an element of unintentional found in the hostilities which the legal facts contained in the BAP, Eron was sentenced to 4 (four) years in prison for being proven against article 351 concerning severe maltreatment resulting in death. The research method used in studying and discussing this problem is normative juridical. The legal materials used are primary, secondary and tertiary legal materials. The results of the research on the elements of Article 351 of the Criminal Code in the decision No. 1/P.B/2022/Pn.Amb did not comply, this is because the decision did not find the element intentionally and accurately. Then the thing that became the basis for the Panel of Judges to sentence the perpetrators was the demands of the Public Prosecutor and by considering every piece of evidence in the dispute, the intentional intentional counter-attack can be interpreted as a form of overmacht or what is called the influence of coercive force.